A method for preparing a modified polypropylene composite

CN122917352APending Publication Date: 2026-10-16GUANGZHOU SHENGFENG PLASTIC TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611369820.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-04
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0006]为此,本发明提供一种改性聚丙烯复合材料的制备方法,用以解决现有技术中玻纤增强聚丙烯复合材料需依赖偶联剂、相容剂等多类助剂导致配方复杂、成本高,且常规宽范围配方及单一温区工艺条件下玻纤分散不均匀、保留长度短、产品力学性能批次稳定性差的技术问题

Benefits of technology

[0016] Compared with existing technologies, the advantages of this invention are as follows: This invention systematically optimizes five dimensions: formulation ratio, mixing method, temperature control strategy, cooling process, and sieving accuracy. In these five stages, stepwise mixing ensures uniform coating of PP particles with calcium carbonate, providing a foundation for subsequent glass fiber dispersion. Stepped temperature control ensures full melting of PP while maximizing the preservation of glass fiber length, maintaining the uniform dispersion formed during the mixing stage. The combination of water cooling and air cooling prevents defects in the strip-shaped material due to thermal shock, protecting the dispersed glass fiber from secondary agglomeration during cooling. Precise sieving ultimately ensures consistent product particle size, resulting in consistent glass fiber content in each particle during downstream processing. These five stages, sequentially transmitted and cumulatively optimized along the process flow, collectively enable the preparation of modified polypropylene composite materials with uniform glass fiber dispersion, excellent mechanical properties, and good particle size consistency without the addition of any coupling agents, compatibilizers, or toughening agents, effectively overcoming many technical difficulties existing in existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122917352A_ABST
    Figure CN122917352A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of high polymer composite material, and particularly relates to a preparation method of modified polypropylene composite material, which comprises the following steps: taking polypropylene 70-80%, calcium carbonate 10-15%, glass fiber 15-20% and color sand 0.2-0.5% by mass percentage, pre-mixing the polypropylene and the calcium carbonate, then adding the glass fiber and the color sand and mixing them uniformly; sending the mixed ingredients into a double-screw extruder, and melting and mixing them through six-stage temperature zones; water-cooling and air-cooling them in sequence after extruding and drawing; screening them through a double-layer vibrating screen after cutting, and obtaining modified polypropylene particles with a particle size of 3-5 mm. The present application does not need to add a coupling agent, the components are uniformly dispersed, the product has excellent mechanical properties, and has the advantages of low cost and stable process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer composite materials technology, and specifically to a method for preparing a modified polypropylene composite material. Background Technology

[0002] Polypropylene (PP), as a general-purpose thermoplastic, has advantages such as low density, good chemical resistance, excellent electrical insulation, and good processing performance, and is widely used in automobiles, home appliances, building materials, packaging, and other fields. However, pure polypropylene materials have defects such as low strength, insufficient rigidity, poor heat resistance, and large molding shrinkage, which limit its application in high-end fields such as load-bearing structural components.

[0003] To improve the mechanical properties of polypropylene, existing technologies typically employ reinforcement modification using glass fibers. Glass fiber filling significantly enhances the overall mechanical properties of polypropylene composites, showing notable improvements in tensile strength, impact strength, and flexural strength. However, simply adding glass fibers presents the following problems: (1) The interfacial bonding force between glass fiber and polypropylene matrix is ​​weak, which affects the reinforcement effect; (2) When the amount of glass fiber added is too high, the material becomes more brittle and its impact toughness decreases; (3) Glass fiber reinforced PP has poor surface gloss and is prone to "floating fiber" phenomenon; (4) The material cost is relatively high.

[0004] Chinese patent CN109370049A, published on February 22, 2019, discloses a reinforced and toughened glass fiber / PP composite material comprising 70%–80% highly crystalline PP, 10%–20% short glass fibers, 5%–15% nano-calcium carbonate, 0.1%–0.5% coupling agent, and 0.05%–0.75% superdispersant. Another patent discloses a reinforced and toughened modified polypropylene composite material for filter plates, comprising 50%–70% polypropylene resin, 10%–30% long glass fibers, and 10%–20% surface-modified calcium carbonate, among other components.

[0005] However, existing technologies still have the following shortcomings: (1) The formulation usually requires the addition of various additives such as coupling agents, compatibilizers, and toughening agents, resulting in complex components and high costs; (2) The temperature zone control in the preparation process is not precise enough, which affects the uniformity of glass fiber dispersion and the overall performance of the material; (3) There is a lack of complete optimization schemes for parameters of each step in the entire preparation process. Summary of the Invention

[0006] Therefore, this invention provides a method for preparing modified polypropylene composite materials to solve the technical problems in the prior art where glass fiber reinforced polypropylene composite materials rely on multiple additives such as coupling agents and compatibilizers, resulting in complex formulations, high costs, and uneven glass fiber dispersion, short retention length, and poor batch stability of product mechanical properties under conventional wide-range formulations and single-temperature zone processes. To achieve the above objective, this invention provides a method for preparing modified polypropylene composite materials, characterized by comprising the following steps: Step S1: Weigh polypropylene, calcium carbonate, glass fiber and colored sand according to a preset ratio, mix them evenly to obtain a mixed ingredient. The raw materials do not contain coupling agents, compatibilizers and toughening agents. Step S2: The mixed ingredients are fed into the hopper of the extrusion equipment for melting and mixing to obtain a molten mixture. The extrusion equipment is provided with multiple temperature zones along the material travel direction. Step S3: The molten and mixed material is extruded through an extruder head to form a strip. Step S4: The strip is subjected to water cooling and air cooling in sequence to obtain a cooled strip. Step S5: Cut the cooled strip into pellets to obtain granules; Step S6: The granules are conveyed to a vibrating screen for screening to remove unqualified initial granules and obtain modified polypropylene granules. Step S7: Store and package the modified polypropylene granules.

[0007] Further, in step S1, the mass percentage of polypropylene in the mixed ingredients is 70% to 80%, the mass percentage of calcium carbonate is 10% to 15%, the mass percentage of glass fiber is 15% to 20%, the mass percentage of colored sand is 0.2% to 0.5%, and the total mass percentage of polypropylene, calcium carbonate, glass fiber and colored sand is 100%.

[0008] Furthermore, in step S1, polypropylene and calcium carbonate are first mixed to form a first mixture, and then glass fiber and colored sand are added to the first mixture for further mixing.

[0009] Furthermore, in step S2, during the melt mixing process, the mixed ingredients sequentially pass through six temperature zones with temperatures of 250°C, 260°C, 270°C, 260°C, 240°C, and 220°C.

[0010] Furthermore, in step S2, the melt mixing is carried out by the screw of an extrusion device, which shears and mixes the ingredients to disperse the glass fiber and calcium carbonate in the polypropylene matrix.

[0011] Furthermore, in step S3, during the extrusion process of the molten and mixed material through the extruder head, the extrusion pressure is 3MPa to 8MPa, the diameter of the formed strip is 2.6mm to 2.8mm, and the extrusion speed is 1 ton / hour.

[0012] Further, in step S4, the water cooling and air cooling process includes: sequentially introducing the strip into a water cooling tank for water cooling and then into an air cooling device for air cooling, to obtain a cooled strip with a temperature of 40℃~60℃; the cooling water temperature in the water cooling tank is 20℃~35℃, and the residence time of the strip in the water cooling tank is 2~4 seconds; the air cooling device cools the strip with a wind speed of 15m / s~25m / s, and the air cooling residence time is 1.5~3 seconds.

[0013] Furthermore, in step S5, during the pelletizing process, the cooled strip is conveyed along its length to the pelletizer, and the pelletizer cuts the strip into multiple pellets.

[0014] Furthermore, in step S6, the screening process uses a vibrating screen to screen the pellets obtained from pelletizing to obtain qualified particles with a particle size of 3mm to 5mm.

[0015] Furthermore, the composite particles comprise a polypropylene matrix and glass fibers and calcium carbonate particles dispersed in the polypropylene matrix, wherein the average retention length of the glass fibers in the composite particles is 1.0 mm to 2.5 mm.

[0016] Compared with existing technologies, the advantages of this invention are as follows: This invention systematically optimizes five dimensions: formulation ratio, mixing method, temperature control strategy, cooling process, and sieving accuracy. In these five stages, stepwise mixing ensures uniform coating of PP particles with calcium carbonate, providing a foundation for subsequent glass fiber dispersion. Stepped temperature control ensures full melting of PP while maximizing the preservation of glass fiber length, maintaining the uniform dispersion formed during the mixing stage. The combination of water cooling and air cooling prevents defects in the strip-shaped material due to thermal shock, protecting the dispersed glass fiber from secondary agglomeration during cooling. Precise sieving ultimately ensures consistent product particle size, resulting in consistent glass fiber content in each particle during downstream processing. These five stages, sequentially transmitted and cumulatively optimized along the process flow, collectively enable the preparation of modified polypropylene composite materials with uniform glass fiber dispersion, excellent mechanical properties, and good particle size consistency without the addition of any coupling agents, compatibilizers, or toughening agents, effectively overcoming many technical difficulties existing in existing technologies.

[0017] Furthermore, addressing the technical problem in existing technologies where glass fibers easily entangle and agglomerate when directly mixed with other components, making uniform dispersion difficult, this invention employs a step-by-step mixing method. First, polypropylene and calcium carbonate are pre-mixed, allowing calcium carbonate powder to pre-coat the surface of the polypropylene particles, forming a physical isolation layer. Then, glass fibers are added for secondary mixing, utilizing the barrier effect of calcium carbonate to effectively inhibit the entanglement and agglomeration of the glass fibers. Comparative studies show that, compared to single-stage mixing, step-by-step mixing reduces the coefficient of variation of calcium carbonate from 8.5% to 2.0% and improves the glass fiber dispersion grade from C to A.

[0018] Furthermore, addressing the technical problem that existing technologies using single-temperature or simple two-stage temperature control cannot simultaneously meet the dual requirements of sufficient melting and protection of glass fibers, this invention employs a six-stage stepped temperature control scheme with a gradual increase followed by a decrease. The initial stage gradually increases the temperature to 270℃ to ensure sufficient melting of polypropylene and impregnation of the glass fibers, while the subsequent stage gradually decreases the temperature to prevent thermal degradation of the polypropylene and protect the glass fibers from excessive shearing. Comparative examples show that, compared to a constant temperature of 260℃, this scheme increases the retained glass fiber length from 1.2 mm to 2.1 mm, while simultaneously reducing the melt index (MFI) from 9.8 g / 10 min to 8.5 g / 10 min and the color difference from 2.8 to 1.2. This demonstrates that the stepped temperature control scheme of this invention effectively inhibits PP thermal degradation and improves the uniformity of glass fiber dispersion.

[0019] Furthermore, addressing the technical problems of existing technologies where single water cooling easily leads to thermal shock deformation and surface water residue, and single air cooling is inefficient and space-consuming, this invention adopts a cooling method of first water cooling and then air cooling. The water cooling temperature is 20℃~35℃ with a residence time of 2~4 seconds, while the air cooling wind speed is 15m / s~25m / s with a residence time of 1.5~3 seconds. This allows the strip-shaped material to be rapidly shaped by water cooling, have surface moisture removed by a water absorption device, and then be uniformly cooled to 40℃~60℃ by air cooling. Comparative examples show that, compared with single water cooling, this method reduces the roundness deviation of the strip-shaped material from 0.25mm to 0.04mm, the surface crack rate from 30% to 0%, and the breakage rate from 10 times / hour to 0 times / hour.

[0020] Furthermore, addressing the technical problem in existing technologies where insufficient screening precision leads to poor particle size consistency and affects the stability of downstream processing, this invention employs a double-layer vibrating screen with 4 mesh and 8 mesh to precisely screen the pelletized material. The oversize material (>4.75mm) and undersize material (<2.36mm) are discharged as unqualified products, while qualified particles with a particle size of 2.36mm to 4.75mm are collected, achieving a particle size qualification rate of over 98%. Attached Figure Description

[0021] Figure 1 This is a flowchart of the preparation method of the modified polypropylene composite material in this embodiment; Figure 2This is a flowchart of the ingredient preparation and mixing steps in this embodiment; Figure 3 This is a flowchart of the melt mixing and extrusion steps in this embodiment; Figure 4 This is a flowchart of the extrusion and fiber drawing steps in this embodiment; Figure 5 This is a flowchart of the steps for the combined water cooling and air cooling in this embodiment. Detailed Implementation

[0022] To make the objectives and advantages of the present invention clearer, the present invention will be further described below with reference to embodiments; it should be understood that the specific embodiments described herein are merely for explaining the present invention and are not intended to limit the present invention.

[0023] Please see Figure 1 The diagram shown is a flowchart of the preparation method of the modified polypropylene composite material in this embodiment.

[0024] This invention provides a method for preparing a modified polypropylene composite material, comprising: Step S1: Weigh 70%–80% polypropylene, 10%–15% calcium carbonate, 15%–20% glass fiber, and 0.2%–0.5% colored sand according to a predetermined ratio. Add the polypropylene and calcium carbonate to a high-speed mixer and premix for 2–3 minutes at 650–700 rpm. Then add the glass fiber and colored sand, and continue mixing for 3–5 minutes at 650–700 rpm until the material is visually uniform in color and free of agglomerates, thus obtaining the mixed batch. The mixed batch is then conveyed to the main feed hopper of the extrusion equipment via a screw feeder. The colored sand refers to a granular plastic colorant composed of a colorant (pigment or dye), carrier resin, and dispersant, and its form is coarse powder or microbead particles, distinct from traditional powdered pigments and masterbatches. The total mixing time in the high-speed mixer is controlled to be 5–8 minutes.

[0025] Please see Figure 2 This is a flowchart of the ingredient preparation and mixing steps in this embodiment.

[0026] In this embodiment, step S1 includes the following specific steps: Step S11: Weigh out 70%–80% polypropylene, 10%–15% calcium carbonate, 15%–20% glass fiber, and 0.2%–0.5% colored sand according to the proportions, with the sum of the mass percentages of each component being 100%. Step S12: Add the weighed polypropylene and calcium carbonate to a high-speed mixer and premix for 2 to 3 minutes at a speed of 650 rpm to 700 rpm. Step S13: Add the weighed glass fiber and colored sand to the high-speed mixer and continue mixing at 650 rpm to 700 rpm for 3 to 5 minutes. Step S14: Visually inspect the mixture until the material is uniform in color and free of agglomerates to obtain the mixed ingredients; Step S15: The mixed ingredients are conveyed to the main feed hopper of the extrusion equipment via a screw feeder; In this embodiment, a high-speed mixer is used as the mixing equipment. Polypropylene and calcium carbonate are first added to the high-speed mixer and premixed for 2-3 minutes at 650-700 rpm, allowing the calcium carbonate powder to initially adhere to the surface of the polypropylene particles. Then, glass fiber and colored sand are added, and mixing continues at 650-700 rpm for 3-5 minutes until the material is visually uniform in color and free of agglomerates, resulting in a mixed batch. Finally, the mixed batch is conveyed to the main feed hopper of the extrusion equipment via a screw feeder. This step-by-step feeding method utilizes the coating effect of calcium carbonate powder on the polypropylene surface during premixing. When glass fiber is subsequently added, the calcium carbonate particles adhering to the polypropylene surface act as physical separators and lubricants under mechanical stirring, effectively reducing direct contact and entanglement between glass fibers. Simultaneously, the strong shearing force of the high-speed mixer ensures that the colored sand is evenly distributed on the matrix surface, guaranteeing product color consistency. The screw feeder uses a closed conveying system, preventing dust dispersion and material stratification.

[0027] Understandably, in the industrial mixing process of modified plastics, glass fibers, in their loose bundle or flocculent form, are prone to entanglement and agglomeration when directly mixed with other components. This leads to uneven dispersion of glass fibers during subsequent extrusion, thus affecting the batch stability of the product's mechanical properties. Traditional one-time feeding methods struggle to solve this problem. By pre-mixing powdered calcium carbonate with polypropylene, allowing the calcium carbonate to pre-coat the polypropylene surface, and then adding glass fibers for secondary mixing, the "isolation" effect of the calcium carbonate powder between the polypropylene and glass fibers effectively inhibits the entanglement and agglomeration of glass fibers. Simultaneously, high-speed stirring provides sufficient shear dispersion force, ensuring uniform spreading of the colored sand, while the closed-loop spiral feeding ensures the homogeneity of the mixed components and avoids grading during transport. The synergistic effect of these technologies enables good dispersion of glass fibers in the matrix, ensuring the uniformity and stability of product performance. Furthermore, it eliminates the need for additional special dispersion equipment, offering the advantages of simple process and suitability for continuous industrial production.

[0028] Specifically, in step S1, the mass percentage of polypropylene in the mixed ingredients is 70% to 80%, the mass percentage of calcium carbonate is 10% to 15%, the mass percentage of glass fiber is 15% to 20%, the mass percentage of colored sand is 0.2% to 0.5%, and the total mass percentage of polypropylene, calcium carbonate, glass fiber and colored sand is 100%.

[0029] To demonstrate the beneficial effects of the proportions of each component in the mixture, examples and comparative examples were set up, and the following experiments were conducted: In the formulation system of this embodiment, polypropylene (PP) serves as the matrix resin and is the core component that determines the basic mechanical properties and processability of the composite material; glass fiber serves as the reinforcing phase and is the core component that determines the upper limit of the mechanical properties of the composite material; colored sand only serves a coloring function and has a very low content (0.2% to 0.5%), which has no effect on mechanical properties, so it is fixed at 0.5% in the experimental design; calcium carbonate serves as a rigid filler to improve the rigidity and dimensional stability of the material, and on the other hand, it is pre-coated on the surface of polypropylene particles during the stepwise feeding process, which plays a physical isolation role for the subsequently added glass fiber and inhibits the entanglement and agglomeration of glass fiber, so its content needs to be maintained in the range of 10% to 15%.

[0030] Based on the functional positioning of the components mentioned above, the following design principles were adopted when setting up the embodiments and comparative examples: the content of PP and glass fiber was determined first to cover the upper, middle and lower limits of the range, the colored sand was fixed at 0.5%, and the remainder was made up to 100% by calcium carbonate.

[0031] It should be noted that in the formulation system defined in this embodiment (PP 70%–80%, calcium carbonate 10%–15%, glass fiber 15%–20%, colored sand 0.2%–0.5%), due to the lower limit constraints of each component, PP and glass fiber cannot simultaneously approach their respective upper limits without restriction. When PP exceeds 74%–75%, even if calcium carbonate is taken as the lower limit of 10% and colored sand is taken as 0.5%, the remaining space is insufficient to accommodate the lower limit requirement of 15% for glass fiber. Therefore, in the following embodiments, 74% PP is the actual operable upper limit under the premise of ensuring glass fiber ≥15% and calcium carbonate ≥10%. This fact itself proves the criticality of the stated ratio range.

[0032] In Example 1-1, the mass percentage of polypropylene is 73%, the mass percentage of calcium carbonate is 11.5%, the mass percentage of glass fiber is 15%, the mass percentage of colored sand is 0.5%, and the sum of the mass percentages of all components is 100%.

[0033] In Examples 1-2, the mass percentage of polypropylene is 70%, the mass percentage of calcium carbonate is 14.5%, the mass percentage of glass fiber is 15%, the mass percentage of colored sand is 0.5%, and the sum of the mass percentages of all components is 100%.

[0034] In Examples 1-3, the mass percentage of polypropylene is 74%, the mass percentage of calcium carbonate is 10.5%, the mass percentage of glass fiber is 15%, the mass percentage of colored sand is 0.5%, and the sum of the mass percentages of all components is 100%.

[0035] In Comparative Example 1-1, the mass percentage of polypropylene is 69%, the mass percentage of calcium carbonate is 14.5%, the mass percentage of glass fiber is 16%, the mass percentage of colored sand is 0.5%, and the sum of the mass percentages of all components is 100%.

[0036] In Comparative Examples 1-2, the mass percentage of polypropylene was 81%, calcium carbonate was 3.5%, glass fiber was 15%, and colored sand was 0.5%, with the sum of the mass percentages of all components being 100%. The homogeneity of the mixtures from each example and comparative example was tested using the following method: for each test, 10 samples (approximately 50g each) were taken at equal time intervals along the mixer's discharge time axis to eliminate sampling randomness.

[0037] (a) Testing the uniformity of colored sand dispersion Spread each sample (approximately 50g) evenly on a white background and visually observe the distribution of the colored sand particles under a standard light source. Grade the distribution as follows: Grade 1: Completely uniform distribution, consistent color, and no identifiable agglomerates; Grade 2: Uniform distribution with occasional isolated colored spots (≤2 per 50g sample); Grade 3: Basically uniform distribution with a small number of visible colored spots (3–5 per 50g sample); Grade 4: Uneven distribution with many visible colored spots (6–10 per 50g sample); Grade 5: Severely uneven distribution with obvious colored clumps (>10 per 50g sample).

[0038] (II) Detection of the uniformity of calcium carbonate distribution The determination was performed according to ISO 11358 "Thermogravimetric analysis of plastic polymers". Approximately 10 mg of each sample was placed in the thermogravimetric analyzer and heated from room temperature to 900°C at a rate of 10°C / min under a nitrogen atmosphere. The mass change curve of the sample as a function of temperature (TG curve) was recorded.

[0039] On the TG curve, the decomposition of calcium carbonate corresponds to a mass loss (CO2 release) in the temperature range of 600–800℃. The calcium carbonate content is calculated using the following formula:

[0040] Where, Δm 600~800℃ The values ​​represent the mass loss in the 600–800℃ range, m0 represents the initial mass of the sample, 100 represents the molecular weight of CaCO3, and 44 represents the molecular weight of CO2.

[0041] The mean, standard deviation (SD), and coefficient of variation (CV) of the calcium carbonate content determination results of 10 samples were calculated. CV = SD / mean × 100%. The evaluation criteria were: CV ≤ 3% for excellent mixing uniformity, 3% < CV ≤ 5% for good, and CV > 5% for unqualified.

[0042] (III) Detection of glass fiber dispersion state Take a small amount (approximately 2g) of each sample and spread it evenly on a glass slide. Under an optical microscope (magnification 40–100x), randomly observe 10 fields of view and record the dispersion state of the glass fibers in each field of view. Evaluate according to the following grades: Grade A: Fibers are uniformly dispersed in monofilaments with no visible aggregates; Grade B: Fibers are basically dispersed with occasional small aggregates (<0.5mm); Grade C: Fibers are partially dispersed with many visible aggregates (0.5–2mm); Grade D: Fibers are poorly dispersed with a large number of entangled aggregates (>2mm).

[0043] (iv) Comprehensive Judgment Criteria Based on the above three testing indicators, the following comprehensive judgment criteria are established: "Excellent": Simultaneously meets the following requirements: colored sand dispersion grade ≤ 2, calcium carbonate coefficient of variation (CV) ≤ 3%, and glass fiber dispersion grade ≥ B.

[0044] "Poor": If any of the above three indicators fails to meet the "Excellent" standard, it is judged as "Poor".

[0045] Specifically, in step S1, polypropylene and calcium carbonate are first mixed to form a first mixture, and then glass fiber and colored sand are added to the first mixture for further mixing.

[0046] The results are shown in Table 1, which is a data table of the uniformity test results of the mixed ingredients under different formulation ratios.

[0047] Table 1. Results of homogeneity testing of mixed ingredients under different formulation ratios.

[0048] It can be seen from the above table: (1) The dispersion grade of the colored sand in Examples 1-1 to 1-3 is all grade 1, indicating that the colored sand can achieve complete uniform dispersion under standard mixing conditions at a content of 0.5%. The colored sand content in Comparative Examples 1-1 and 1-2 is 0.5%, and the dispersion grade is also grade 1, indicating that the colored sand can always achieve uniform dispersion at a content of 0.5%, and the performance degradation of the comparative examples is unrelated to the colored sand.

[0049] (2) The coefficient of variation (CV) of calcium carbonate content in Examples 1-1 to 1-3 was ≤2.5%, which is far better than the industry standard of 3%, indicating that calcium carbonate was highly uniformly distributed in each example. The CV of Comparative Example 1-1 was 6.7%, which is about 3 times that of the examples, indicating that when the PP content is less than 70%, the volume fraction of the polypropylene matrix is ​​insufficient and cannot effectively coat and isolate the calcium carbonate particles, resulting in a significant deterioration in its distribution uniformity. In Comparative Example 1-2, the PP content was as high as 81%, and the calcium carbonate was compressed to only 3.5%. The physical isolation and filling reinforcement effects of calcium carbonate were basically lost, and the uniformity evaluation was unqualified.

[0050] (3) The glass fiber dispersion grades of Examples 1-1 to 1-3 are all Grade A, with the fibers uniformly dispersed in the PP matrix as monofilaments, thanks to the sufficient coating and isolation effect of calcium carbonate in the range of 10.5% to 14.5%. The glass fiber dispersion grade of Comparative Example 1-1 is Grade C, because the insufficient PP prevents the matrix from effectively isolating the glass fiber monofilaments. The glass fiber dispersion grade of Comparative Example 1-2 is Grade B, with basically good glass fiber dispersion. This is because the glass fiber content is still maintained at 15%, but the calcium carbonate content is only 3.5%, and the physical isolation and filling reinforcement effect of calcium carbonate is basically lost, and the integrity and stability of the system have been destroyed.

[0051] (4) Based on the comprehensive evaluation of the three indicators, the comprehensive evaluation of Examples 1-1 to 1-3 is "excellent", while the comprehensive evaluation of Comparative Examples 1-1 to 1-2 is "poor". The above results show that when the polypropylene content is 70-74%, the calcium carbonate content is 10.5%-14.5%, the glass fiber content is 15%, and the colored sand content is 0.5%, the four components can achieve good dispersion in the mixing process of step S1. The calcium carbonate is uniformly distributed in the matrix (CV≤3%), the colored sand is completely dispersed without agglomeration (Grade 1), and the glass fiber is uniformly dispersed in monofilament form without entanglement (Grade A), providing a highly uniform mixing basis for subsequent melt mixing and extrusion drawing.

[0052] In Comparative Example 1-1, the polypropylene content was 69%, and the contents of calcium carbonate, glass fiber, and colored sand all fell within the stated range. However, the CV of calcium carbonate reached 6.7%, and the dispersion of glass fiber dropped to grade C, resulting in an overall assessment of "poor." In Comparative Example 1-2, the polypropylene content was 81%. Although the contents of glass fiber and colored sand remained unchanged, the excessively high PP ratio compressed calcium carbonate to 3.5%, far below the lower limit of 10%. The physical isolation and reinforcing effects of calcium carbonate were essentially lost, and the integrity and stability of the system were compromised, resulting in an overall assessment of "poor." The above results indicate that once the polypropylene content is below 70% or above 80%, even if the glass fiber and colored sand remain within the stated range, the mixing uniformity still experiences a significant drop (when PP is insufficient, the CV of calcium carbonate increases sharply to 6.7%, and the dispersion of glass fiber drops to grade C; when PP is excessively high, calcium carbonate is compressed to 3.5%, and the CV reaches 10.3%), demonstrating the criticality and inventiveness of the polypropylene content range selection in this invention.

[0053] Step S2: The mixed ingredients are fed into the hopper of an extrusion device for melt mixing. A twin-screw extruder is used as the melt mixing device. The twin-screw extruder has six temperature zones arranged sequentially along the material travel direction. The temperatures of each zone are: Zone 1 250℃, Zone 2 260℃, Zone 3 270℃, Zone 4 260℃, Zone 5 240℃, and Zone 6 220℃. The main motor speed of the twin-screw extruder is 300-400 rpm. After the mixed ingredients enter the twin-screw extruder through the main feed hopper, they are conveyed forward under the shearing and mixing action of the screws, sequentially passing through the above six temperature zones for melt mixing.

[0054] Please see Figure 3 This is a flowchart of the melt mixing and extrusion steps in this embodiment.

[0055] In this embodiment, step S2 includes the following specific steps: Step S21: A twin-screw extruder is provided as a melt mixing device. The twin-screw extruder has six temperature zones arranged sequentially along the material travel direction. The temperatures of each temperature zone are: Zone 1 250℃, Zone 2 260℃, Zone 3 270℃, Zone 4 260℃, Zone 5 240℃, and Zone 6 220℃. The main engine speed of the twin-screw extruder is set to 300rpm~400rpm.

[0056] Step S22: The mixed ingredients are fed into the twin-screw extruder through the main feed hopper.

[0057] In step S23, the mixed ingredients are conveyed forward in the twin-screw extruder under the shearing and mixing action of the screws, and are melt-mixed sequentially through the above six temperature zones.

[0058] Step S24: After melting and mixing, a molten mixture is obtained and output from the extruder outlet.

[0059] In this embodiment, zones one to three are the melting and plasticizing sections, where the temperature gradually increases from 250°C to 270°C, causing the polypropylene matrix to soften and fully melt. At the same time, the melt impregnates and encapsulates the glass fiber and calcium carbonate. Zone four is the homogenization section, where the temperature drops to 260°C, making the melt temperature more uniform and continuing to mix and disperse. Zones five and six are the cooling and venting sections, where the temperature drops from 240°C to 220°C. On the one hand, this moderately lowers the melt temperature to facilitate subsequent extrusion molding. On the other hand, the lower temperature helps to expel volatile gases and moisture entrained in the melt, avoiding the formation of bubbles or pores in the extruded strips.

[0060] Understandably, existing single or two-stage temperature control solutions struggle to balance the conflict between ensuring complete melting of polypropylene and protecting glass fiber from heat. A six-stage stepped temperature control system, employing initial heating to ensure complete melting and wetting, followed by gradual cooling to prevent glass fiber degradation and thermo-oxidative aging, combined with twin-screw shearing and mixing, achieves uniform glass fiber dispersion while preserving its effective length. This provides a homogeneous and stable melt for subsequent fiber drawing, offering the advantages of precise temperature control, good glass fiber length retention, and stable product quality.

[0061] Specifically, in step S2, during the melt mixing process, the mixed ingredients sequentially pass through six temperature zones with temperatures of 250°C, 260°C, 270°C, 260°C, 240°C, and 220°C.

[0062] To demonstrate the beneficial effects of temperature zone setting, the following experiments were conducted in both the embodiment and the comparative example: In Example 2-1, the twin-screw extruder is set with six temperature zones in sequence along the material travel direction. The temperatures of each temperature zone are 250℃, 260℃, 270℃, 260℃, 240℃ and 220℃, respectively. The mixed ingredients are melted and mixed in the above six temperature zones in sequence. After step S2 is completed, samples are taken for testing.

[0063] In Comparative Example 2-1, the temperature zones of the twin-screw extruder along the material travel direction were all set to a constant temperature of 260°C, and the rest was the same as in Example 2-1.

[0064] In Comparative Example 2-2, the temperature of the twin-screw extruder gradually increases along the material travel direction, with temperatures of 220°C, 230°C, 240°C, 250°C, 260°C and 270°C in each temperature zone, and the rest is the same as in Example 2-1.

[0065] In Comparative Examples 2-3, the temperature of the twin-screw extruder gradually decreased along the material travel direction, with temperatures of 270°C, 260°C, 250°C, 240°C, 230°C, and 220°C in each temperature zone, and the rest was the same as in Example 2-1.

[0066] After the various embodiments and comparative examples are melt-mixed in step S2, the melt mixture is sampled and tested at the extruder outlet. Five samples are taken for each test and the average value is taken.

[0067] (a) Appearance inspection of molten mixtures Observe the color, uniformity, and bubble condition of the molten mixture directly at the extruder outlet and evaluate it according to the following grades: Grade A: uniform color, no visible unmelted particles, no bubbles; Grade B: basically uniform color, occasional unmelted particles or bubbles; Grade C: uneven color, many visible unmelted particles or bubbles; Grade D: significantly uneven color, a large number of unmelted particles or bubbles, obvious discoloration or charring spots.

[0068] (ii) Fiberglass retention length testing Take an appropriate amount of each molten mixture sample and place it in a muffle furnace. Calcinate at 600℃ for 2 hours to remove the resin matrix. Take the remaining glass fibers and place them under an optical microscope (magnification 100-400 times). Randomly measure the length of no less than 200 fibers and take their arithmetic mean, which is recorded as the average retained length of the glass fiber (mm).

[0069] (III) Melt Flow Index (MFI) Testing The testing was conducted according to GB / T 3682 standard. Melt index (g / 10min) was measured for each molten mixture sample under a load of 2.16 kg at 230℃. MFI reflects the molecular weight and degree of degradation of the polymer: an excessively high MFI indicates that the polymer has undergone thermal degradation and its molecular weight has decreased significantly; an excessively low MFI indicates insufficient melting. Comparative literature reports also confirm that MFI gradually increases with increasing processing temperature, and polymer degradation intensifies when the temperature exceeds a certain range. This invention will verify the beneficial effect of stepwise temperature control on inhibiting the thermal degradation of PP through the MFI index.

[0070] (iv) Color difference value (ΔE) detection The testing was conducted according to GB / T 7921 standard. Samples of each molten mixture were taken, and the color difference value (ΔE) was measured using a colorimeter, with pure PP granules as a blank control. A smaller ΔE value indicates more uniform dispersion of the colored sand and that no thermal discoloration occurred during the melting process. When ΔE > 3.0, the color difference is clearly visible to the naked eye, indicating poor dispersion of the colored sand or thermal oxidation discoloration of the PP.

[0071] The experimental results are shown in Table 2, which is a data table of performance test results of molten mixtures under different temperature control modes.

[0072] Table 2. Performance test results of molten mixtures under different temperature control modes.

[0073] It can be seen from the above table: (1) Comparison of the appearance of the molten mixture. The molten mixture of Example 2-1 has a uniform white appearance, with no unmelted particles, no bubbles, and no discoloration or charring, and is rated as Grade A. The molten mixture of Comparative Example 2-2 (continuous heating) is yellowish and uneven in color, with more unmelted particles and bubbles, and slight charring spots, and is rated as Grade C. Comparative Example 2-1 and Comparative Example 2-3 are both Grade B. The former is because the temperature is uniform in each temperature zone, and PP did not reach the optimal temperature window for full melting in the three zones, with occasional unmelted particles and a small number of bubbles; the latter is slightly yellow because the PP surface has undergone slight thermal oxidation due to the high temperature of 270℃ in the first stage.

[0074] (2) Comparison of glass fiber retention length. The average glass fiber retention length of Example 2-1 was 2.1 mm, which was significantly better than that of Comparative Examples 2-1, 2-2, and 2-3. Comparative Example 2-2 was continuously heated to 270°C. Although the high temperature in the latter part reduced the melt viscosity, it also aggravated the thermal degradation of PP (MFI reached 15.2), resulting in a decrease in the binding force of the melt on the glass fiber, making the glass fiber more prone to breakage under screw shear. The constant temperature of 260°C in Comparative Example 2-1 was too low, the PP was not fully melted, the melt viscosity was too high, and the shear stress on the glass fiber in the screw was too large, resulting in a retention length of only 1.2 mm. Although the continuous cooling of Comparative Example 2-3 had low temperature protection in the latter part, the high temperature in the former part had already caused irreversible thermal damage to the PP, and the melt viscosity in the high temperature zone in the former part was too low, resulting in severe breakage of the glass fiber under shear. Only Example 2-1, through a temperature control strategy of gradually increasing the temperature to 270°C in the first stage and then gradually decreasing it to 220°C in the second stage, ensures that the PP is fully melted and then rapidly cools down. This avoids both insufficient melting in the constant temperature scheme and thermal degradation in the continuous heating scheme, thus maximizing the retained length of the glass fiber.

[0075] (3) Comparison of Melt Flow Index (MFI). The MFI of Example 2-1 was 8.5 g / 10 min, which is within the normal range for modified PP materials. The MFI of Comparative Example 2-2 was as high as 15.2 g / 10 min, indicating that PP underwent significant thermal degradation during the continuous heating to 270℃, and the molecular chain breakage led to an abnormally high fluidity. The MFI of Comparative Example 2-3 was 12.6 g / 10 min, and the high temperature of 270℃ in the initial stage also led to thermal degradation of PP. The MFI of Comparative Example 2-1 was 9.8 g / 10 min, which was slightly higher than that of Example 2-1, indicating that although PP did not undergo serious thermal degradation under the constant temperature of 260℃, the low temperature led to insufficient melting and poor wetting effect of the melt on glass fiber, which is consistent with the test results of low glass fiber retention length.

[0076] (4) Color difference value (ΔE) comparison. The ΔE of Example 2-1 is 1.2, and the color difference is almost indistinguishable to the naked eye, indicating that the colored sand is completely dispersed in the molten mixture and the PP has not undergone thermal oxidation discoloration. The ΔE of Comparative Example 2-2 is 6.5 (>3.0), and the color difference is clearly distinguishable to the naked eye, indicating that the continuous heating to 270℃ caused thermal oxidation discoloration of the PP. At the same time, the colored sand may decompose or migrate at high temperature, further aggravating the color unevenness. The ΔE of Comparative Example 2-3 is 4.3 (>3.0), and the initial high temperature of 270℃ also caused thermal oxidation discoloration of the PP. The ΔE of Comparative Example 2-1 is 2.8 (close to the critical value of 3.0), indicating that although the constant temperature of 260℃ did not cause obvious thermal oxidation discoloration, the dispersion uniformity of the colored sand at a slightly lower temperature was not as good as that of the Example.

[0077] (5) Considering all five indicators, the appearance (Grade A), glass fiber retention length (2.1 mm), MFI (8.5 g / 10 min), and color difference value (1.2) of the melt mixture in Example 2-1 were significantly better than those of the three comparative examples. The above results show that only when the extruder adopts a six-stage stepped temperature control scheme along the material travel direction can the glass fiber be effectively protected from excessive shearing and breakage and the PP thermal degradation be avoided, while ensuring that the PP is fully melted and the color sand is evenly dispersed, thus obtaining a melt mixture with uniform appearance, intact glass fiber retention, moderate melt fluidity, and pure color. The constant temperature of 260℃ resulted in insufficient melting and a low glass fiber retention length; continuous heating caused severe thermal degradation of PP (MFI=15.2, ΔE=6.5), leading to melt deterioration; continuous cooling caused thermal damage due to the high temperature in the previous stage (MFI=12.6, ΔE=4.3). None of the three comparative schemes could achieve the technical effect of the present invention, demonstrating the criticality and inventiveness of the six-stage stepped temperature control scheme of the present invention.

[0078] Specifically, in step S2, the melt mixing is carried out by the screw of an extrusion device, which shears and mixes the ingredients to disperse the glass fiber and calcium carbonate in the polypropylene matrix.

[0079] Step S3: The molten mixture is extruded through the end die of a twin-screw extruder to form a strip. An extrusion die is provided at the end die, with multiple circular orifices having a diameter of 2.6mm to 2.8mm. The molten mixture is extruded into a strip by the screw pushing the material through the orifices. During extrusion, the extrusion pressure is controlled at 3MPa to 8MPa, and the extrusion speed (i.e., the extruder's discharge rate) is controlled at 1 ton / hour. The extruded strip is stretched by a traction device, with the traction speed matched to the extrusion speed to ensure the strip diameter is stably controlled at 2.6mm to 2.8mm. A filter screen and a flow divider are provided in front of the extrusion die. The filter screen has a mesh size of 80 to 120 mesh to filter out any unmelted particles or impurities that may be present in the melt. The flow divider is used to evenly distribute the melt to each orifice, ensuring uniform discharge from each orifice.

[0080] Please see Figure 4 This is a flowchart of the extrusion and fiber drawing steps in an embodiment of the present invention.

[0081] In this embodiment, step S3 specifically includes: Step S31: An extrusion die is set at the end of the twin-screw extruder. The extrusion die has 8 to 12 circular orifices, each with a diameter of 2.6 mm to 2.8 mm. A filter screen and a flow divider are set in front of the extrusion die. The filter screen has a mesh size of 80 to 120.

[0082] Step S32: Set the extrusion pressure to 3MPa~8MPa and the extrusion speed to 1 ton / hour.

[0083] In step S33, the molten mixture is pushed by the screw and filtered through a filter screen to remove unmelted granules or impurities. Then, it is evenly distributed to each die by a distributor plate and extruded through the die to form strips.

[0084] In step S34, the extruded strip is stretched by a traction device. The traction speed is controlled at 150m / min to 250m / min, and the traction speed is matched with the extrusion speed so that the diameter of the strip is stably controlled at 2.6mm to 2.8mm.

[0085] Understandably, excessively low or high extrusion pressure can lead to surface defects and diameter fluctuations in the strips, while improper extrusion speed can cause problems such as strip breakage or insufficient cooling. By controlling the extrusion pressure at 3–8 MPa and the extrusion speed at 1 ton / hour, the two work together to ensure the melt passes stably through the die. The diameter of the strips is precisely controlled by the traction device, while the purity of the melt and the uniformity of the output from each die are ensured by the use of a filter screen and a flow divider. This ensures that the strips have a regular cross-section, a smooth surface, and stable diameter tolerance, providing reliable strip raw materials for subsequent cooling and pelletizing. This method has the beneficial effects of dimensional stability, good surface quality, and low breakage rate.

[0086] Specifically, in step S3, during the extrusion process of the molten and mixed material through the extruder head, the extrusion pressure is 3MPa to 8MPa, the diameter of the formed strip is 2.6mm to 2.8mm, and the extrusion speed is 1 ton / hour.

[0087] Step S4 involves sequentially subjecting the strip-shaped material to water cooling and air cooling. Water cooling involves introducing the strip-shaped material into a water cooling tank, where the cooling water temperature is controlled at 20℃~35℃. The cooling water circulates, and the strip-shaped material travels 4~6 meters in the tank, with a residence time of 2~4 seconds, allowing the surface of the strip-shaped material to cool and solidify rapidly. Air cooling involves introducing the water-cooled strip-shaped material into an air cooling device. This device has multiple sets of air nozzles arranged sequentially along the direction of the strip-shaped material's movement. The air blown from the nozzles is at room temperature (25℃~30℃) and has a wind speed of 15m / s~25m / s. The strip-shaped material travels 3~5 meters in the air cooling device, with a residence time of 1.5~3 seconds, reducing the surface temperature of the strip-shaped material to 40℃~60℃. While the core temperature remains higher than the surface, the surface has been sufficiently hardened and solidified, meeting the requirements for surface hardness and conveying stability in the pelletizing process. The outlet of the water-cooled tank is also equipped with a water suction device (such as a water-absorbing sponge or air knife) to remove the moisture adhering to the surface of the strip-shaped material, so as to prevent the strip-shaped material from carrying moisture into the air-cooling section and affecting the air-cooling effect.

[0088] Please see Figure 5 This is a flowchart of the combined water-cooling and air-cooling steps in this embodiment.

[0089] In this embodiment, step S4 includes the following specific steps: Step S41: Provide a water-cooled tank and an air-cooled device, and install a water suction device at the outlet of the water-cooled tank; the air-cooled device is provided with multiple sets of air nozzles in sequence along the traveling direction of the strip.

[0090] Step S42: Set the cooling water temperature in the water-cooling tank to 20℃~35℃, the travel length of the strip in the water-cooling tank to 4~6 meters, and the residence time to 2~4 seconds; set the air temperature blown out by the blower nozzle to room temperature (25℃~30℃), the wind speed to 15m / s~25m / s, and the travel length of the strip in the air-cooling device to 3~5 meters and the residence time to 1.5~3 seconds.

[0091] Step S43: The strip is introduced into a water-cooling tank for cooling. The cooling water is circulated to rapidly cool and solidify the surface of the strip.

[0092] Step S44: After the strip leaves the water-cooling tank, the water adhering to the surface of the strip is removed by the water suction device at the outlet of the water-cooling tank.

[0093] In step S45, the strip-shaped material after water cooling and dehydration is introduced into the air cooling device, and air blown out by multiple sets of air nozzles is used to cool the strip-shaped material, so that the surface temperature of the strip-shaped material is uniformly reduced to 40℃~60℃, and the cooled strip-shaped material is obtained.

[0094] In this embodiment, due to the low thermal diffusivity of polypropylene, the cooling medium mainly acts on the surface of the strip within a few seconds of cooling, while the core temperature remains approximately 10°C to 20°C higher than the surface temperature, resulting in a radial temperature gradient within the strip. However, the surface has already sufficiently hardened and set, adequately meeting the requirements for surface hardness and conveying stability in the pelletizing process. The higher core temperature actually helps the strip maintain its flexibility during pelletizing, preventing fragmentation due to excessive brittleness. After pelletizing, the particles cool naturally in the air, with internal heat continuing to conduct outwards, eventually leading to a more uniform overall temperature.

[0095] It is understandable that the temperature of the extruded strips exiting the die head can reach over 200℃, requiring rapid cooling to a suitable pelletizing temperature. However, water cooling alone can easily lead to thermal shock deformation and residual water on the surface, while air cooling alone is inefficient and requires a large footprint. This solution employs a two-step cooling process: water cooling followed by air cooling. The high thermal conductivity of the water cooling section allows for rapid surface shaping of the strips to prevent sagging and deformation, with the water temperature controlled between 20℃ and 35℃ to balance the cooling rate and thermal shock stress. The air cooling section uses high-speed airflow to achieve uniform cooling, eliminate residual internal heat, and dry surface moisture. A water absorption device prevents water residue from affecting the uniformity of subsequent air cooling. This solution enables rapid surface cooling and shaping of the strips within a short stroke, uniformly reducing the surface temperature to 40℃–60℃ while simultaneously drying residual surface moisture, meeting the requirements for surface hardness and dryness for subsequent pelletizing. It should be noted that, due to the low thermal diffusivity of polypropylene, the cooling medium primarily acts on the surface of the strips during the initial cooling period of a few seconds. The core temperature remains approximately 10°C to 20°C higher than the surface temperature, resulting in a radial temperature gradient within the strips. However, the surface has already sufficiently hardened and set, adequately meeting the requirements for surface hardness and conveying stability in the pelletizing process. The higher core temperature actually helps the strips maintain flexibility during pelletizing, preventing breakage due to excessive brittleness. After pelletizing, the particles cool naturally in the air, with internal heat continuing to conduct outwards, eventually leading to a more uniform overall temperature.

[0096] Specifically, in step S4, the water cooling and air cooling process includes: sequentially introducing the strip into a water cooling tank for water cooling and then into an air cooling device for air cooling, so that the surface temperature of the strip is reduced to 40℃~60℃; the cooling water temperature in the water cooling tank is 20℃~35℃, and the residence time of the strip in the water cooling tank is 2~4 seconds; the air cooling device cools the strip at a wind speed of 15m / s~25m / s, and the air cooling residence time is 1.5~3 seconds.

[0097] To verify the beneficial effect of the combination of water cooling and air cooling parameters on the cooling effect of strip-shaped materials, the following experiments were conducted in both the example and comparative examples: In Example 3-1, the water cooling temperature was 27.5℃, the water cooling residence time was 3 seconds, the air cooling wind speed was 20m / s, and the air cooling residence time was 2 seconds.

[0098] In Example 3-2, the water cooling temperature was 20°C, the water cooling residence time was 2 seconds, the air cooling wind speed was 15 m / s, and the air cooling residence time was 1.5 seconds.

[0099] In Example 3-3, the water cooling temperature is 35℃, the water cooling residence time is 4 seconds, the air cooling wind speed is 25m / s, and the air cooling residence time is 3 seconds.

[0100] In Comparative Example 3-1, the water cooling temperature was 10℃, the water cooling residence time was 0.5 seconds, the air cooling wind speed was 5m / s, and the air cooling residence time was 1 second.

[0101] In Comparative Example 3-2, the water cooling temperature was 45℃, the water cooling residence time was 8 seconds, the air cooling wind speed was 35m / s, and the air cooling residence time was 4 seconds.

[0102] The strips of each embodiment and comparative example, after being cooled in step S4, were subjected to quality testing in the following manner: for each test, 10 test points were equidistantly distributed along the length of the strip, and the average value was taken.

[0103] (a) Detection of roundness deviation of strip-shaped objects The diameter of the strip was measured using a vernier caliper (accuracy 0.02 mm). Ten measurement points were taken every meter along the strip's length. The diameter was measured twice at 90° intervals around each point. The difference between the maximum and minimum diameters at each point was calculated, and the average of the ten measurements was taken as the roundness deviation (mm). A smaller roundness deviation indicates a more regular cross-section and better cooling uniformity. A roundness deviation ≤ 0.1 mm is considered acceptable.

[0104] (ii) Detection of surface cracks in strip-shaped objects The surface of the strip was visually inspected using a 10x magnifying glass, segment by segment, for surface cracks. The number of cracked test points was recorded, and the crack rate was calculated as (number of cracked points / total number of test points × 100%). Surface microcracks are a direct reflection of thermal shock stress; a lower crack rate indicates better control of thermal stress during the cooling process. A crack rate of 0% is considered acceptable.

[0105] (iii) Temperature detection of strips after cooling At the outlet of the air cooling device, an infrared thermometer (with an accuracy of ±0.5°C) is used to measure the surface temperature of the strand. One detection point is taken per meter along the length direction of the strand, for a total of 10 points, and the average value is taken as the temperature of the strand after cooling (°C). A temperature in the range of 40°C to 60°C after cooling is qualified — if the temperature is too high, the strand has insufficient hardness and is prone to deformation and adhesion during subsequent pelletizing; if the temperature is too low, the strand is too brittle and prone to generating debris during pelletizing.

[0106] (4) Detection of surface dryness of the strand The filter paper wiping method is adopted: a dry filter paper is gently pressed against the surface of the strand, and it is observed whether there are wet marks on the filter paper. One detection point is taken per meter along the length direction of the strand, for a total of 10 points. The number of detection points with wet marks is recorded, and the surface wetness rate is calculated (number of wet points / total number of detection points × 100%). A lower surface wetness rate indicates a better air cooling and drying effect. A surface wetness rate of 0% is qualified.

[0107] (5) Statistics of strand breakage rate During the continuous operation of the extrusion wire drawing in step S3 and the cooling in step S4, the number of strand breaks within 1 hour is counted, and the strand breakage rate (times / hour) is calculated. The strand breakage rate is a comprehensive index reflecting the matching degree of cooling parameters. When the cooling is insufficient, the strand has insufficient strength and is easily broken by stretching; when the cooling is excessive, the strand becomes brittle and is also easily broken during the traction process. A strand breakage rate ≤ 3 times / hour is qualified, and > 3 times / hour is unqualified. This criterion is determined according to the generally accepted industry standard for the continuous and stable operation of extrusion granulation production lines (the number of strand breaks per hour is usually required not to exceed 3 times).

[0108] (6) Comprehensive judgment criteria Based on the above 5 detection indexes, the following comprehensive judgment criteria are formulated: "Excellent": Simultaneously meet the requirements that the roundness deviation ≤ 0.1 mm, the surface crack rate is 0%, the temperature after cooling is 40 to 60°C, the surface wetness rate is 0%, and the strand breakage rate ≤ 3 times / hour.

[0109] "Poor": If any one of the above five indexes does not meet the "excellent" standard, it is judged as "poor".

[0110] The experimental results are shown in Table 3, which is a data table of the quality detection results of the strands under different cooling parameter combinations.

[0111] Table 3 Data table of quality detection results of strands under different cooling parameter combinations

[0112] It can be seen from the above table that: (1) Comparison of roundness deviation of strips. The roundness deviation of Examples 3-1 to 3-3 was 0.04 mm to 0.06 mm, which was far better than the qualified standard of 0.1 mm, indicating that the cross-section of the strips was regular and the cooling was uniform. The roundness deviation of Comparative Example 3-1 was 0.28 mm and that of Comparative Example 3-2 was 0.35 mm, which were significantly worse than the Examples. In Comparative Example 3-1, the surface of the strips suddenly contracted due to the low temperature of the cooling water and the short residence time, resulting in uneven internal stress and cross-sectional deformation. In Comparative Example 3-2, the strips were immersed in the water cooling tank for a long time. After the surface was over-cooled, the inside remained at a high temperature. The large temperature difference between the inside and outside caused warping and deformation.

[0113] (2) Surface Crack Rate Comparison: The surface crack rates of Examples 3-1 to 3-3 were all 0%, indicating that no thermal shock cracks were generated. The surface crack rate of Comparative Example 3-1 reached 40%, mainly because the water cooling temperature was too low, and the rapid cooling of the strip generated a large thermal shock stress, which exceeded the tensile strength of the PP material, resulting in the generation of surface microcracks. These microcracks will become stress concentration points and potential failure sources in subsequent use. Although Comparative Example 3-2 did not have the problem of excessively low water cooling temperature, the excessively high air cooling wind speed and excessively long air cooling time caused the strip to become brittle after excessive cooling. Microcracks will also be generated during the traction process. Although the crack rate of Comparative Example 3-2 was 0% in this experiment, its excessively low temperature has already led to an increase in the brittleness of the strip, and a large amount of debris is expected to be generated during subsequent pelletizing.

[0114] (3) Comparison of cooling temperatures. The cooling temperatures of Examples 3-1 to 3-3 were 48℃ to 58℃, all falling within the suitable pelleting temperature window of 40℃ to 60℃. The cooling temperature of Comparative Example 3-1 was 72℃, which is higher than the upper limit of 60℃. The strips were still at a relatively high temperature when they exited the cooling section, resulting in insufficient hardness. They were prone to deformation and adhesion during subsequent conveying and pelleting, which seriously affected the pelleting quality. The cooling temperature of Comparative Example 3-2 was only 35℃, which is lower than the lower limit of 40℃. The strips became brittle due to overcooling, and debris and dust were easily generated during pelleting. At the same time, the low temperature also indicated that the cooling medium was consumed too much and the energy consumption was too high.

[0115] (4) Comparison of surface dryness. The surface wettability of Examples 3-1 to 3-3 was 0%, indicating that the strips were completely dry after air cooling. The surface wettability of Comparative Example 3-1 reached 60%, because the air cooling speed was too low and the residence time was too short, which could not effectively blow away the moisture adhering to the surface of the strips in the water cooling section. The residual moisture may cause the particles to absorb moisture or surface defects during subsequent storage and transportation. The surface wettability of Comparative Example 3-2 was 100%, because the water cooling time was too long, resulting in a large amount of water accumulating on the surface of the strips. Although the air cooling speed was high, the amount of water was too large to be completely removed within the limited air cooling section.

[0116] (5) Comparison of breakage rates. The breakage rates of Examples 3-1 to 3-3 were 0 to 1 times / hour, indicating that the extrusion and drawing process was stable. The breakage rate of Comparative Example 3-1 was as high as 8 times / hour. The main reasons were: firstly, insufficient cooling led to excessively high temperature of the strip and insufficient melt strength, making it easy to break under traction force; secondly, excessive surface moisture caused slippage between the strip and the traction roller, and tension fluctuations induced breakage. The breakage rate of Comparative Example 3-2 was 5 times / hour, mainly because the strip became brittle due to overcooling, and was prone to brittle fracture during bending and traction.

[0117] (6) Considering all five indicators, the roundness deviation, surface crack rate, post-cooling temperature, surface wettability, and breakage rate of Examples 3-1 to 3-3 were significantly better than those of Comparative Examples 3-1 to 3-2. The above results indicate that only when the water cooling temperature, water cooling residence time, air cooling speed, and air cooling residence time are controlled within the ranges of 20℃ to 35℃, 2 to 4 seconds, 15 m / s to 25 m / s, and 1.5 to 3 seconds, respectively, and when combined with strips with a diameter of 2.6 mm to 2.8 mm, can the strips maintain a regular circular cross-section after cooling, be free of thermal shock cracks, uniformly drop to the suitable pelletizing temperature window of 40℃ to 60℃, and have a completely dry surface with no residual moisture, while ensuring stable operation of the extrusion and fiber drawing process. Comparative Example 3-1 suffered from excessively high temperature, surface wettability, and frequent breakage due to insufficient cooling and inadequate drying; Comparative Example 3-2 suffered from strip deformation, excessively low temperature, and increased brittleness due to over-cooling. The two pairs of proportions demonstrate from both upper and lower limits that the cooling parameter combination of the present invention has criticality. If any parameter or all parameters are below the lower limit or above the upper limit, it is impossible to simultaneously meet the comprehensive quality requirements of no deformation, no cracks, suitable temperature, dry surface, and stable operation of the strip. This reflects the creativity and industrial applicability of the cooling parameter system selection of the present invention.

[0118] Step S5: The cooled strip is continuously conveyed along its length to a pelletizer for pelletizing. The pelletizer is a rotary cutter type, including a traction roller assembly, a rotating cutter roller, and a fixed cutter. The traction roller assembly feeds the strip into the pelletizer at a rate matching the extrusion speed. The strip is pressed by the traction roller assembly into the shearing zone between the rotating cutter roller and the fixed cutter. The rotating cutter roller is equipped with 4-6 rotating blades, and its rotation speed is 200-300 rpm. The fixed cutter is fixedly installed on the pelletizer frame, and the gap between the rotating blade and the fixed cutter is 0.05mm-0.15mm. Through the shearing action of the rotating blade and the fixed cutter, the strip is cut into multiple pellets with a length of 3mm-5mm. A dust collector is installed above the pelletizer, connected to an exhaust system, to collect dust and debris generated during the pelletizing process.

[0119] Understandably, pelleting quality directly affects the product's particle size qualification rate and appearance quality. Existing technologies often suffer from uneven particle length due to a mismatch between feeding speed and pelleting speed, and rough cross-sections due to improper blade clearance. By using a traction roller assembly that is stably fed in accordance with the extrusion speed, constant tension conveying of the strips is ensured; a rotating cutter roller, operating at 200-300 rpm in conjunction with a fixed cutter, maintains a blade clearance of 0.05mm-0.15mm to ensure a clean cut and uniform particle length of 3mm-5mm; a dust collector promptly removes dust. These combined measures result in uniform particle size, clean cross-sections, and low dust content, providing high-quality particles for subsequent screening.

[0120] Specifically, in step S5, during the pelletizing process, the cooled strip is conveyed along its length to the pelletizer, which then cuts the strip into multiple pellets.

[0121] Step S6: The granules are conveyed to a vibrating screen via a pneumatic conveying system for screening. The vibrating screen is a multi-layer vibrating screen, preferably a two-layer vibrating screen, with a first screen and a second screen arranged sequentially from top to bottom. The first screen has a mesh size of 4 (screen opening size of 4.75 mm) and is used to intercept oversized particles larger than 4.75 mm; the second screen has a mesh size of 8 (screen opening size of 2.36 mm) and is used to remove oversized particles and debris smaller than 2.36 mm. The vibration frequency of the vibrating screen is 900 rpm to 1200 rpm, the amplitude is 3 mm to 5 mm, and the screen surface inclination angle is 5° to 10°. After the granules enter the vibrating screen, they pass through each screen layer sequentially under vibration: oversized particles larger than 4.75mm are intercepted by the first screen and discharged as defective products for collection, which can be returned for crushing and re-granulation; qualified particles with a size of 2.36mm to 4.75mm pass through the first screen and are intercepted by the second screen, collected from the qualified material outlet, resulting in modified polypropylene granules. Since the granules obtained from pelletizing are not perfectly spherical, after screening by the 4-mesh and 8-mesh double-layer vibrating screens, the nominal particle size corresponding to the 2.36mm to 4.75mm particles is 3mm to 5mm, which is understandable and achievable by those skilled in the art. Debris and dust smaller than 2.36mm pass through the second screen and are discharged from the bottom fine material outlet for collection, treated as waste. The target particle size of the modified polypropylene granules obtained after screening is 3 to 5mm.

[0122] Understandably, excessively large particles, debris, and dust mixed in with the pelleted material need to be removed by screening to ensure product quality. Existing technologies often suffer from poor grading accuracy and easy screen clogging due to unreasonable screen mesh size and vibration parameters. By using a combination of an upper 4-mesh screen and a lower 8-mesh screen, the acceptable particle size range of 2.36mm to 4.75mm is precisely defined; vibration parameters of 900rpm to 1200rpm, amplitude of 3mm to 5mm, and inclination angle of 5° to 10° ensure sufficient grading of the pellets without causing secondary damage; a pneumatic conveying system achieves closed and efficient conveying with an air velocity of 15m / s to 20m / s and a material-to-air ratio of 10kg / kg to 20kg / kg; and a sealed cover and dust collection pipe effectively collect dust. These combined methods enable precise control of the product particle size within 3mm to 5mm, resulting in accurate particle size control, high screening efficiency, and low dust pollution.

[0123] Specifically, in step S6, the screening process uses a vibrating screen to screen the pellets obtained from pelletizing to obtain qualified particles with a particle size of 3mm to 5mm.

[0124] In step S7, the modified polypropylene granules are transported to a storage silo for storage and packaged for shipment as needed. The storage silo is a sealed stainless steel silo with an inlet and a dust-removing breather valve at the top and an outlet at the bottom. During storage, the internal temperature of the storage silo is controlled at 25℃~35℃, and the relative humidity is controlled at ≤60%. The storage time of the granules in the silo does not exceed 72 hours to avoid moisture absorption or aging due to prolonged storage. During packaging, the modified polypropylene granules in the storage silo are discharged into an automatic packaging machine through the outlet. The automatic packaging machine includes a weighing mechanism, a bag feeding mechanism, and a sealing mechanism. The weighing accuracy of the weighing mechanism is ±0.1kg, and quantitative weighing is performed according to the standard weight of 25kg per bag. After weighing, the material falls into the packaging bag through the discharge port. The packaging bag has a double-layer structure of a woven bag with a PE film lining. The inner PE film bag is used for moisture protection, and the outer woven bag is used to provide mechanical strength. The sealing mechanism uses heat sealing to seal the PE film bags at a temperature of 150℃~200℃ for 1~3 seconds. After sealing, the bag opening is sewn shut. The packaged bags are then conveyed to the palletizing area, where an automatic palletizer stacks 5 bags per layer, with 8~10 layers per stack. After stacking, the bags are wrapped with stretch film to secure the stack before being transferred to the finished goods warehouse for shipment. Each batch of packaging bags has a product label affixed or printed on its outer surface. The label includes information such as product name, batch number, production date, net content, and specifications to ensure product traceability.

[0125] It is understandable that modified polypropylene granules are prone to absorbing moisture during storage, leading to defects such as silver streaks and bubbles in downstream injection molded products. Prolonged storage may also result in oxidative degradation. Existing technologies often suffer from product quality deterioration and difficulties in quality management due to improper temperature and humidity control during storage, poor packaging sealing, and a lack of traceability markings. By controlling the temperature and humidity of the storage silo at 25℃~35℃ and ≤60% respectively, and limiting the storage time to no more than 72 hours, the moisture absorption and oxidative degradation of the granules are effectively inhibited, ensuring timely material turnover. Double-layer packaging bags, combining heat sealing and stitching, with a heat sealing temperature of 150~200℃ and a time of 1~3 seconds, ensure a firm seal without damaging the film, achieving reliable moisture protection. Automatic packaging machines accurately weigh to ensure consistent net content, and stacking and wrapping ensure stable stacks for easy transportation. Product labels provide a unique identifier for each batch, enabling full-process quality traceability. These combined measures ensure stable product quality, reliable packaging sealing, and information traceability during storage and packaging, offering the beneficial effects of moisture and oxidation prevention, high packaging efficiency, and strong traceability.

[0126] Specifically, the composite particles comprise a polypropylene matrix and glass fibers and calcium carbonate particles dispersed in the polypropylene matrix, wherein the average retention length of the glass fibers in the composite particles is 1.0 to 2.5 mm.

[0127] Example: Step S1: Weigh out 73% polypropylene, 10.15% calcium carbonate, 16.5% glass fiber, and 0.35% colored sand by mass percentage, with the sum of the mass percentages of each component being 100%. Add the weighed polypropylene and calcium carbonate to a high-speed mixer and premix for 2-3 minutes at 650-700 rpm. Add the weighed glass fiber and colored sand to the high-speed mixer and continue mixing for 3-5 minutes at 650-700 rpm. Visually inspect the mixture until the material has a uniform color and no agglomerates, thus obtaining the mixed batch. Convey the mixed batch to the main feed hopper of the extrusion equipment via a screw feeder.

[0128] Step S2: A twin-screw extruder is provided as the melt mixing equipment. The twin-screw extruder has six temperature zones arranged sequentially along the material travel direction, with the following temperatures: Zone 1 250℃, Zone 2 260℃, Zone 3 270℃, Zone 4 260℃, Zone 5 240℃, and Zone 6 220℃. The main motor speed of the twin-screw extruder is set to 300 rpm to 400 rpm. The mixed ingredients are fed into the twin-screw extruder through the main feed hopper. In the twin-screw extruder, the mixed ingredients are conveyed forward under the shearing and mixing action of the screws, sequentially passing through the above six temperature zones for melt mixing. After melt mixing, a molten mixture is obtained and output from the extruder outlet.

[0129] Step S3: An extrusion die is installed at the end of the twin-screw extruder. The extrusion die has multiple circular orifices with a diameter of 2.6mm to 2.8mm. A filter screen and a distributor plate are installed in front of the extrusion die. The filter screen has a mesh size of 80 to 120 mesh. The extrusion pressure is set to 3MPa to 8MPa, and the extrusion speed is set to 1 ton / hour. Under the pushing action of the screw, the molten mixture is filtered through the filter screen to remove unmelted particles or impurities, and then evenly distributed to each orifice by the distributor plate. The mixture is then extruded through the orifices to form strips. The extruded strips are then stretched by a traction device at a speed matched to the extrusion speed. The diameter of the strips is 3.2mm, a size achieved by the polypropylene melt leaving the orifice due to the extrusion expansion effect. The orifice diameter is 2.6mm to 2.8mm, and the expansion ratio is approximately 1.14 to 1.23, which is within the conventional polypropylene extrusion expansion range (1.1 to 1.3).

[0130] Step S4: A water-cooled tank and an air-cooling device are provided. A water suction device is installed at the outlet of the water-cooled tank. Multiple sets of air nozzles are sequentially arranged along the direction of travel of the strip. The cooling water temperature in the water-cooled tank is set to 20℃~35℃, the travel length of the strip in the water-cooled tank is 4~6 meters, and the residence time is 2~4 seconds. The air temperature blown out by the air nozzles is set to room temperature (25℃~30℃), the wind speed is 15m / s~25m / s, the travel length of the strip in the air-cooling device is 3~5 meters, and the residence time is 1.5~3 seconds. The strip is introduced into the water-cooled tank for cooling, and the cooling water is circulated to rapidly cool and solidify the surface of the strip. After the strip leaves the water-cooled tank, the water suction device at the outlet of the water-cooled tank removes the moisture adhering to the surface of the strip. After being cooled and dehydrated by water, the strip-shaped material is introduced into an air-cooling device. Air blown out by multiple sets of air nozzles cools the strip-shaped material, causing the internal and external temperatures of the strip-shaped material to drop uniformly to 40℃~60℃, thus obtaining a cooled strip-shaped material.

[0131] Step S5: The cooled strip is continuously conveyed along its length to a pelletizer for pelletizing. The pelletizer is a rotary cutter type, comprising a traction roller assembly, a rotating cutter roller, and a fixed cutter. The traction roller assembly feeds the strip into the pelletizer at a rate matching the extrusion speed. The rotating cutter roller rotates at 200 rpm to 300 rpm, with a gap of 0.05 mm to 0.15 mm between the blades and the fixed cutter. Through shearing action, the strip is cut into pellets with a length of 3 mm to 5 mm. A dust collector hood connected to an exhaust system is installed above the pelletizer to collect dust and debris generated during pelletizing.

[0132] Step S6: Provide a vibrating screen, which is a two-layer vibrating screen, with a first screen and a second screen arranged sequentially from top to bottom; the first screen has a mesh size of 4 mesh (screen aperture size of 4.75mm), and the second screen has a mesh size of 8 mesh (screen aperture size of 2.36mm). Set the vibration frequency of the vibrating screen to 900rpm~1200rpm, the amplitude to 3mm~5mm, and the screen surface inclination angle to 5°~10°. The pelletized material is conveyed to the vibrating screen via a pneumatic conveying system, with a conveying air velocity of 15m / s~20m / s and a material-to-air ratio of 10kg / kg~20kg / kg. After the granules enter the vibrating screen, they are classified sequentially through each layer of screens under vibration: oversized particles larger than 4.75mm are intercepted by the first screen and discharged as defective products; qualified particles with a size of 2.36mm to 4.75mm pass through the first screen and are intercepted by the second screen, collected from the qualified material outlet, resulting in modified polypropylene granules; debris and dust smaller than 2.36mm pass through the second screen and are discharged from the bottom fine material outlet. A sealed cover is installed above the vibrating screen and connected to a dust collection pipe; dust generated during the screening process is extracted and discharged through the dust collection pipe.

[0133] Step S7: The qualified modified polypropylene granules obtained after screening are transported to a stainless steel sealed storage silo for storage. The temperature inside the silo is controlled at 25℃~35℃, and the relative humidity is ≤60%. The storage time does not exceed 72 hours. During packaging, the granules are weighed quantitatively at 25kg per bag with a weighing accuracy of ±0.1kg using an automatic packaging machine. They are then placed into double-layered packaging bags lined with PE film and heat-sealed at 150℃~200℃ for 1~3 seconds before sealing. The opening of the woven bag is then sewn shut. After packaging, labels containing the product name, production batch number, production date, net content, and specifications are affixed or printed. After stacking and wrapping, the granules are stored in the warehouse for shipment.

[0134] Comparative Example 1: 0.3% of coupling agent (KH-550 silane coupling agent) was added to the mixed ingredients in step S1, and the polypropylene content was reduced accordingly to keep the total amount at 100%. The remaining steps and parameters were the same as in the example.

[0135] Comparative Example 2: In step S1, instead of using a step-by-step feeding method, all four materials—polypropylene, calcium carbonate, glass fiber, and colored sand—are added to a high-speed mixer at once for mixing. The remaining steps and parameters are the same as in the example.

[0136] Comparative Example 3: In step S2, the temperature zones of the twin-screw extruder along the material travel direction were all set to a constant temperature of 260°C, and the remaining steps and parameters were the same as in the example.

[0137] Comparative Example 4: In step S4, only water cooling is used, without air cooling. The travel length of the strip in the water cooling tank is extended to 8-10 meters and the residence time is extended to 6-8 seconds, so that the strip is fully cooled to near the pelletizing temperature in the water cooling tank. The remaining steps and parameters are the same as in the example.

[0138] Comparative Example 5: The particle size collected after vibrating sieving in step S6 is 2mm to 4mm, which is not the target particle size of 3mm to 5mm. The remaining steps and parameters are the same as in the example.

[0139] Detection methods and detection indicators The modified polypropylene particles prepared by the complete process in Examples 1-5 and Comparative Examples 1-5 were subjected to quality testing according to the following methods. Five samples were taken for each test and the average value was taken.

[0140] (a) Testing the uniformity of mixed ingredients Dispersion grade of colored sand: Refer to the method of GB / T 18251-2019, take the mixed material and observe it visually under a standard light source, and score it according to grades 1 to 5 (grade 1 is the best).

[0141] Calcium carbonate coefficient of variation (CV): The calcium carbonate content was determined by thermogravimetric analysis (TGA), and the coefficient of variation of 10 samples was calculated. CV ≤ 3% is considered excellent.

[0142] Glass fiber dispersion grade: Observed under an optical microscope (40-100x), and rated as A to D (Grade A is the best).

[0143] (ii) Quality inspection of molten mixture Appearance of the molten mixture: Observe directly at the extruder outlet and evaluate according to grades A to D (grade A is the best).

[0144] Average fiberglass retention length: After calcining in a muffle furnace at 600℃ for 2 hours to remove resin, the length of at least 200 fibers was measured under a microscope and the average value (mm) was taken.

[0145] Melt Flow Index (MFI): Measured according to GB / T 3682, at 230℃ and 2.16kg (g / 10min), reflecting the degree of PP degradation.

[0146] Color difference value (ΔE): Refer to GB / T 7921, with pure PP granules as a blank control, ΔE>3.0 is a color difference that can be distinguished by the naked eye.

[0147] (III) Quality inspection of strips after cooling Roundness deviation of strip-shaped objects: Measure the diameter with vernier calipers, take 10 points along the length direction, and calculate the difference (mm) between the maximum and minimum diameters. ≤0.1mm is acceptable.

[0148] Surface crack rate: Observe with a 10x magnifying glass and record the percentage of cracked points (%). 0% is acceptable.

[0149] Temperature after cooling: The surface temperature of the strip is measured by an infrared thermometer (°C), and 40°C to 60°C is considered acceptable.

[0150] Surface wettability: Filter paper wiping method, record the percentage of points with wettability (%), 0% is acceptable.

[0151] Breakage rate: The number of times a strip breaks within 1 hour (times / hour).

[0152] (iv) Final product performance testing Particle size qualification rate: Take 100 particles, measure their length, and calculate the percentage (%) of particles in the range of 3mm to 5mm.

[0153] Tensile strength: Tested according to GB / T 1040 standard (MPa).

[0154] Bending strength: Tested according to GB / T 9341 standard (MPa).

[0155] Notched impact strength: Tested according to GB / T 1043 standard (kJ / m) 2 ).

[0156] Product appearance: Visually inspect whether the particles are stuck together, whether the cross-section is neat, and whether there are bubbles or silver streaks on the surface.

[0157] The experimental results are shown in Table 4, which is a comparison table of the test results of the examples and comparative examples at each process stage.

[0158] Table 4. Comparison of test results at each process stage in the examples and comparative examples.

[0159] It can be seen from the above table: (1) Addition or absence of coupling agent. After adding 0.3% KH-550 silane coupling agent to Comparative Example 1, the various test indicators were basically equivalent to those of the Example, with differences within the experimental error range. This shows that the present invention, through specific formulation ratios and process coordination, can achieve mechanical properties equivalent to those of the coupling agent-added scheme without adding any coupling agent. However, Comparative Example 1 requires the addition of an additional coupling agent, making the formulation more complex and increasing raw material costs by about 3-5%. Moreover, an additional auxiliary agent means an additional quality control variable. The Example achieved the same technical effect through a simplified formulation, proving the feasibility and economic advantages of the coupling agent-free scheme of the present invention.

[0160] (2) Effect of stepwise feeding. Comparative Example 2 used a one-time all-inclusive feeding method, resulting in a reduction of the colored sand dispersion grade to level 4, a calcium carbonate CV of 8.5%, a glass fiber dispersion grade to level C, a glass fiber retention length of 1.3 mm, and a final product tensile strength of only 58.3 MPa. This indicates that when feeding all components at once, the glass fiber is added simultaneously, causing entanglement and agglomeration in the initial mixing stage, making it difficult to separate later; and calcium carbonate and colored sand cannot effectively adhere to the PP surface to achieve uniform dispersion. In contrast, this invention premixes calcium carbonate with PP, utilizing the "coating" effect of calcium carbonate powder on the PP surface to form an isolation layer, and then effectively reduces direct contact and entanglement between fibers when glass fiber is added, demonstrating the key contribution of stepwise feeding to dispersion uniformity.

[0161] (3) Effect of stepped temperature control. Comparative Example 3 adopted a constant temperature control scheme of 260℃. The appearance of the molten mixture was grade B (slightly yellow in color, occasional unmelted particles, a small number of bubbles, and no charring). The glass fiber retention length was 1.2 mm, the MFI was 9.8 g / 10 min (slightly higher than the 8.5 g / 10 min of the example, indicating that PP underwent a certain degree of thermal degradation under constant temperature of 260℃), the ΔE was 2.8 (close to the critical value of 3.0, and the color difference was distinguishable), the breakage rate was 6 times / hour, and the tensile strength of the final product was only 52.7 MPa. At a constant temperature of 260℃, although the temperature did not reach the level that would cause severe thermal degradation of PP (MFI of 9.8), the uniform temperature across all zones failed to provide differentiated temperature conditions for different processing stages: the temperature in the melting and plasticizing section was too low (only 260℃), resulting in insufficient PP melting, high melt viscosity, and significant stress on the glass fiber under screw shearing, leading to numerous breakages; the temperature in subsequent sections was also too high, failing to cool down in time to protect the glass fiber and inhibit PP thermo-oxidative aging, thus deteriorating material properties. In contrast, the step-by-step temperature control scheme of this invention, which gradually increases the temperature to 270℃ in the first stage to ensure sufficient PP melting, and then gradually decreases the temperature in the second stage to protect the glass fiber and inhibit PP thermal degradation, allows the PP to cool down rapidly after being fully melted and impregnated with the glass fiber in the first stage. This protects the glass fiber from excessive shearing and avoids prolonged high-temperature degradation of PP, resulting in significantly better overall mechanical properties than the constant temperature 260℃ scheme, demonstrating the unique advantages of the six-stage step-by-step temperature control scheme.

[0162] (4) Effect of water cooling + air cooling combination. Comparative Example 4 only uses water cooling without air cooling. In order to reach a temperature close to that of pelletizing, the water cooling residence time had to be extended to 6-8 seconds, resulting in a roundness deviation of 0.25 mm, a surface crack rate of 30%, a temperature of 38℃ after cooling (below the lower limit of the suitable pelletizing temperature of 40℃, the strips become brittle due to overcooling), a surface wettability of 80%, and a breakage rate as high as 10 times / hour. Water cooling alone causes high-temperature strips to be in contact with cooling water for a long time (6-8 seconds), generating great thermal shock stress, resulting in surface cracks (30%); excessively long water cooling causes the strips to become brittle due to overcooling, resulting in frequent breakage during traction (10 times / hour); and without the air cooling section to dry, a large amount of residual moisture on the surface cannot be removed, resulting in particle adhesion. In contrast, this embodiment uses water cooling followed by air cooling. The water cooling section quickly sets the shape, and the water cooling time is controlled within 2 to 4 seconds to avoid excessive thermal shock. The air cooling section cools the surface evenly and dries it, so that the temperature of the strip is appropriately reduced to 40°C to 60°C. The surface is dry and without residue, which proves the necessity of the water cooling + air cooling combination.

[0163] (5) Effect of target particle size selection. Comparative Example 5 collected particles with a diameter of 2mm to 4mm, and the qualified particle size rate (based on the standard of 3mm to 5mm) was only 70%, with a large number of particles being too small (2mm to 3mm). These small particles melt too quickly in subsequent injection molding, which can easily lead to uneven plasticization and surface defects in the product; at the same time, small particles have a large specific surface area, making them more prone to moisture absorption during storage. Although the mechanical properties of Comparative Example 5 are slightly lower than those of the Example, the difference is not significant, but its excessively wide particle size distribution and poor appearance consistency prove the rationality and necessity of selecting a target particle size of 3mm to 5mm.

[0164] It should be noted that in Comparative Example 5, the mismatch between the pelletizer's feed speed and the cutter roller speed resulted in an excessively wide particle length distribution (2mm–5mm). Although sieved using a 4-mesh / 8-mesh double-layer screen, the particle size classification accuracy was insufficient, with an actual pass rate of only about 70%. This further verifies the necessity of this invention in achieving the target particle size of 3mm–5mm by optimizing pelletizing parameters and using a 4-mesh / 8-mesh double-layer screen. (6) Based on the comprehensive test results, Comparative Examples 1 to 5 provided experimental support in five dimensions: feasibility of no coupling agent, necessity of stepwise feeding, superiority of stepped temperature control, necessity of water-cooling + air-cooling combination, and rationality of target particle size. The five comparative examples demonstrate from different perspectives that each technical feature of the complete technical solution of this invention—stepwise feeding, stepped temperature control, water-cooling + air-cooling combination, and target particle size of 3mm to 5mm—has an independent beneficial effect and works synergistically to achieve uniformly dispersed mixed materials, high-quality molten mixture, regular and dry strips, and modified polypropylene particles with excellent comprehensive mechanical properties. The absence or deviation of any technical feature will lead to significant deterioration in the uniformity, appearance, mechanical properties, or particle size distribution of the intermediate or final product, proving the inventiveness and industrial applicability of the overall technical solution of this invention.

[0165] The technical solution of the present invention has been described above with reference to the preferred embodiments shown in the accompanying drawings. However, it will be readily understood by those skilled in the art that the scope of protection of the present invention is obviously not limited to these specific embodiments. Without departing from the principles of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will all fall within the scope of protection of the present invention.

Claims

1. A method for preparing a modified polypropylene composite material, characterized in that, Includes the following steps: Step S1: Weigh polypropylene, calcium carbonate, glass fiber and colored sand according to a preset ratio, mix them evenly to obtain a mixed ingredient. The raw materials do not contain coupling agents, compatibilizers and toughening agents. Step S2: The mixed ingredients are fed into the hopper of the extrusion equipment and melt-mixed in multiple temperature zones to obtain a molten mixture; Step S3: The molten and mixed material is extruded through an extruder head to form a strip. Step S4: The strip is subjected to water cooling and air cooling in sequence to obtain a cooled strip. Step S5: Cut the cooled strip into pellets to obtain granules; Step S6: The granules are conveyed to a vibrating screen for screening to remove unqualified initial granules and obtain modified polypropylene granules. Step S7: Store and package the modified polypropylene granules.

2. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S1, the mass percentage of polypropylene in the mixed ingredients is 70% to 80%, the mass percentage of calcium carbonate is 10% to 15%, the mass percentage of glass fiber is 15% to 20%, and the mass percentage of colored sand is 0.2% to 0.5%, and the total mass percentage of polypropylene, calcium carbonate, glass fiber and colored sand is 100%.

3. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S1, polypropylene and calcium carbonate are first mixed to form a first mixture, and then glass fiber and colored sand are added to the first mixture for further mixing.

4. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S2, during the melt mixing process, the mixed ingredients sequentially pass through six temperature zones with temperatures of 250°C, 260°C, 270°C, 260°C, 240°C, and 220°C.

5. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S2, the melt mixing is carried out by the screw of the extrusion equipment, which shears and mixes the ingredients to disperse the glass fiber and calcium carbonate in the polypropylene matrix.

6. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S3, during the extrusion process of the molten and mixed material through the extruder head, the extrusion pressure is 3-8 MPa, the diameter of the resulting strip is 2.6-2.8 mm, and the extrusion speed is 1 ton / hour.

7. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S4, the water cooling and air cooling process includes: sequentially introducing the strip into a water cooling tank for water cooling and then into an air cooling device for air cooling, so that the surface temperature of the strip is reduced to 40℃~60℃; the cooling water temperature in the water cooling tank is 20℃~35℃, and the residence time of the strip in the water cooling tank is 2~4 seconds; the air cooling device cools the strip at a wind speed of 15m / s~25m / s, and the air cooling residence time is 1.5~3 seconds.

8. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S5, during the pelletizing process, the cooled strip is conveyed along its length to the pelletizer, which then cuts the strip into multiple pellets.

9. The method for preparing the modified polypropylene composite material according to claim 1, characterized in that, In step S6, the screening process uses a vibrating screen to screen the pellets obtained from pelletizing to obtain qualified particles with a particle size of 3mm to 5mm.

10. A modified polypropylene composite material prepared according to the preparation method of any one of claims 1-9, characterized in that, The composite particles comprise a polypropylene matrix and glass fibers and calcium carbonate particles dispersed in the polypropylene matrix, wherein the average retention length of the glass fibers in the composite particles is 1.0 mm to 2.5 mm.

Citation Information

Patent Citations

  • Enhanced and toughened glass fiber / PP (Polypropylene) composite material and preparation method thereof

    CN109370049A